Le harcèlement psychologique au travail : portrait des recours juridiques au Québec et des décisions rendues par la Commission des lésions professionnelles - Katherine Lippel (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article examines new Quebec legislation establishing the right for all workers to a work environment free of psychological harassment and providing new recourse for its victims. The first part presents an overview of the new legal provisions, while the second part presents the results of a study of Quebec workers’ compensation case law dealing with claims for mental injury related to psychological harassment. All decisions rendered between 1998 and 2002 by the Commission des lésions professionnelles (CLP, the Quebec tribunal with jurisdiction in workers’ compensation issues) were studied (N=108). In 29.6% of the cases, the CLP accepted the claim for compensation, as compared to 52% of the claims for psychological disability attributable to workplace stress other than psychological harassment. Even though the acceptance rate for mental injury attributable to psychological harassment was low, it was much higher than the acceptance rate for the same cases by the Commission de la santé et de la sécurité du travail (CSST) (2.8%). Given that the new legislation limits workers’ rights to monetary damages if the harassment has led to "occupational injury", the article concludes with the hope that this new law can achieve its objectives without the victims’ mental health being at the centre of the case.